Central nervous system interaction and crosstalk between nAChRs and other ionotropic and metabotropic neurotransmitter receptors. (April 2023) - Bono, Federica; Fiorentini, Chiara; Mutti, Veronica; Tomasoni, Zaira; Sbrini, Giulia; Trebesova, Hanna; Marchi, Mario; Grilli, Massimo; Missale, Cristina
Abstract: Neuronal nicotinic acetylcholine receptors (nAChRs) are widely distributed in both the peripheral and the central nervous systems. nAChRs exert a crucial modulatory influence on several brain biological processes; they are involved in a variety of neuronal diseases including Parkinson's disease, Alzheimer's disease, epilepsy, and nicotine addiction. The influence of nAChRs on brain function depends on the activity of other neurotransmitter receptors that co-exist with nAChRs on neurons. In fact, the crosstalk between receptors is an important mechanism of neurotransmission modulation and plasticity. This may be due to converging intracellular pathways but also occurs at the membrane level, because of direct physical interactions between receptors. In this line, this review is dedicated to summarizing how nAChRs and other ionotropic and metabotropic receptors interact and the relevance of nAChRs cross-talks in modulating various neuronal processes ranging from the classical modulation of neurotransmitter release to neuron plasticity and neuroprotection. Graphical Abstract: ga1